Exceptional Changes in Skeletal Anatomy under Domestication: The Case of Brachycephaly. Issue 1 (16th August 2021) - Geiger, M; Schoenebeck, J J; Schneider, R A; Schmidt, M J; Fischer, M S; Sánchez-Villagra, M R
Synopsis: "Brachycephaly" is generally considered a phenotype in which the facial part of the head is pronouncedly shortened. While brachycephaly is characteristic for some domestic varieties and breeds (e.g., Bulldog, Persian cat, Niata cattle, Anglo-Nubian goat, Middle White pig), this phenotype can also be considered pathological. Despite the superficially similar appearance of "brachycephaly" in such varieties and breeds, closer examination reveals that "brachycephaly" includes a variety of different cranial modifications with likely different genetic and developmental underpinnings and related with specific breed histories. We review the various definitions and characteristics associated with brachycephaly in different domesticated species. We discern different types of brachycephaly ("bulldog-type, " "katantognathic, " and "allometric" brachycephaly) and discuss morphological conditions related to brachycephaly, including diseases (e.g., brachycephalic airway obstructive syndrome). Further, we examine the complex underlying genetic and developmental processes and the culturally and developmentally related reasons why brachycephalic varieties may or may not be prevalent in certain domesticated species. Knowledge on patterns and mechanisms associated with brachycephaly is relevant for domestication research, veterinary and human medicine, as well as evolutionary biology, and highlights the profound influence of artificial selection by humans on animal morphology, evolution, and welfare.